2002
DOI: 10.1073/pnas.172700199
|View full text |Cite
|
Sign up to set email alerts
|

Adverse effects of acid rain on the distribution of the Wood ThrushHylocichla mustelinain North America

Abstract: To address the question of the role played by acid rain in population declines of eastern North American songbird species, we combine data from several sources. We use a multiple logistic regression model to test for adverse effects of acid rain on the Wood Thrush, while controlling for regional abundance, landscape-level habitat fragmentation, elevation, soil pH, and vegetation. We show a strong, highly significant, negative effect of acid rain on the predicted probability of breeding by this species, and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 33 publications
(51 reference statements)
1
74
0
Order By: Relevance
“…For example, several studies have found that species such as the Wood Thrush (Hylocichla mustelina), Ovenbird (Seiurus aurocapilla), and American Redstart may be most abundant in mid-successional forests (Holmes et al 1986, Holmes and Sherry 1988, Thompson et al 1992, Hunt 1996, at least in parts of their range, and are less common in the older, more mature stands. The Wood Thrush has received much attention for its widespread declines, including the possible effects of acid rain on eggshell thickness (Hames et al 2002), but less has been said about the possibility that some portion of these declines may be from the maturation of forests in much of its former breeding habitat (Holmes andSherry 2001, Ahlering andFaaborg 2006). Recently, there have been concerns because applications of these models often carried Field of Dreams (''if you build it, they will come'') assumptions (Ahlering and Faaborg 2006), when recent behavioral work suggests that colonization of appropriate habitats may not occur without the proper behavioral cues.…”
Section: Habitat Selection and Suitabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have found that species such as the Wood Thrush (Hylocichla mustelina), Ovenbird (Seiurus aurocapilla), and American Redstart may be most abundant in mid-successional forests (Holmes et al 1986, Holmes and Sherry 1988, Thompson et al 1992, Hunt 1996, at least in parts of their range, and are less common in the older, more mature stands. The Wood Thrush has received much attention for its widespread declines, including the possible effects of acid rain on eggshell thickness (Hames et al 2002), but less has been said about the possibility that some portion of these declines may be from the maturation of forests in much of its former breeding habitat (Holmes andSherry 2001, Ahlering andFaaborg 2006). Recently, there have been concerns because applications of these models often carried Field of Dreams (''if you build it, they will come'') assumptions (Ahlering and Faaborg 2006), when recent behavioral work suggests that colonization of appropriate habitats may not occur without the proper behavioral cues.…”
Section: Habitat Selection and Suitabilitymentioning
confidence: 99%
“…For example, Hames et al (2002) suggested that the widespread decline of the Wood Thrush in the eastern United States is related to eggshell thinning. Their eggshells are thin because of reduced numbers of snails in these forests; snails are rare because of calcium limitations due to acid rain, with populations of Wood Thrush downwind from major industrial regions suffering the most.…”
Section: Ecosystem-level Constraints and Migrant Bird Populationsmentioning
confidence: 99%
“…Earthworms, slugs, millipedes, centipedes, collembolans, and isopods are among the soil animals known to be sensitive to acidity, although most of the studies are from high-deposition areas in Europe (Rusek and Marshall 2000). One recent study reports that productivity of wood thrush (Hylocichla mustelina) populations is negatively correlated with acid deposition levels across the northeastern United States (Hames et al 2002). This is purely a correlative result, but the proposed mechanism for the response is plausible-that acid deposition reduces the quantity or quality of the soil invertebrates that are the main source of calcium for wood thrushes.…”
Section: Forestsmentioning
confidence: 99%
“…Breeding birds have high demands of calcium for eggshell formation and proper juvenile growth. The widespread depletion of environmental calcium availability in northeastern North America is now linked to adverse effects on the distribution of wood thrush (Hylocichla mustelina) (Hames et al, 2002). Unfortunately, the strong link between environmental acidification with MeHg production and calcium depletion may be creating a scenario where their synergy has the potential for long-term, landscape-level impacts on insectivorous passerine populations across much of northeastern North America.…”
Section: Recommended Bioindicatorsmentioning
confidence: 99%